Solitary Waves of the Schrödinger Lattice System with Nonlinear Hopping. (29th April 2015) - Cheng, Ming
Abstract : This paper is concerned with the nonlinear Schrödinger lattice with nonlinear hopping. Via variation approach and the Nehari manifold argument, we obtain two types of solution: periodic ground state and localized ground state. Moreover, we consider the convergence of periodic solutions to the solitary waves.